Peralihan Rezim Tektonik: Implikasinya pada Konsentrasi Torium di Mamasa dan Tana Toraja, Sulawesi-Indonesia - Saputro, Sugeng Purwo; Purwaningsih, Dwi Ratih; Priadi, Bambang (BRIN Publishing, 2020)
Mamasa and Tana Toraja geographically are part of the western arm of Sulawesi Island. The mafic rocks in these areas and their surroundings have high radiation dose rate and thorium (Th) anomaly content. This research aim is to determine tectonic setting mechanism which play the important role on the increasing of Th concentration. Six rock samples were analysed using petrography and geochemical analyses (AAS, ICP-MS, NA, and XRF) completed with the 40K-40Ar dating on selected rock samples. Petrography observations show plagioclase, olivine, pyroxene, hornblende, nepheline, and allanite minerals presence in the rocks which identified as nepheline-basanite, basalt, trachybasalt, and gabbro. Numbers of texture appearances in the rocks indicate contamination and changes on tectonic setting. Geochemistry analysis shows that nepheline-basanite, basalt, trachybasalt, and gabbro (absarokite) were formed at the active continental margin (ACM), which is undergoing active subduction (westward subduction) to post-subduction transition. The changing of tectonic setting made magma solidify in extreme conditions. The magma solidify process is interpreted to occur at the age of 13.10-11.02 Ma. These mechanisms play an important role for the increase of thorium concentration in Mamasa and Tana Toraja.